2022
DOI: 10.1101/2022.05.12.491629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aspects of the glycome of endochondral ossification

Abstract: Comparatively little is known about the glycome (the set of glycans and glycoconjugates made by the cell, tissue or organism) of bone and cartilage. The glycome has a high-density coding capacity and is important in post-translational modification. Lectin histochemistry provides insights into the glycome and we applied this technique to an ectopic ossification site in human bronchial cartilages.Our results show that cartilage matrix at the site of erosion by chondroclasts has a limited but definite glycoprofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, a recent study demonstrated that different lectin immunohistochemistry staining is present in osteoblasts/trabecular bone lining cells, osteocytes, and osteoclasts . Interestingly, they reported that the bone matrix generally did not stain with lectins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent study demonstrated that different lectin immunohistochemistry staining is present in osteoblasts/trabecular bone lining cells, osteocytes, and osteoclasts . Interestingly, they reported that the bone matrix generally did not stain with lectins.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated that different lectin immunohistochemistry staining is present in osteoblasts/ trabecular bone lining cells, osteocytes, and osteoclasts. 36 Interestingly, they reported that the bone matrix generally did not stain with lectins. However, there were non-bisected biand tri-antennary complex-type N-glycans predominantly stained in all of the osteoblast/trabecular bone lining cells, osteocytes, and osteoclasts (via Pisum sativum agglutinin; PSA staining) by showing positive staining of cytoplasm and cell membranes.…”
Section: Histopathological Changes In Cartilage Are Severe In the Med...mentioning
confidence: 99%
See 1 more Smart Citation
“…We applied the lectin lPHA to tissue sections in the present study since we have previously shown that clast and mast cells and endothelial cells stain positively with this lectin (10,11). The specific ligand is the β1-6 branching linkage in complex N-glycans and is formed by the action of N-acetylglucosaminyltransferase-V (GnTase V/MGAT5).…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin wax-embedded tissue blocks were prepared by conventional techniques. Thin sections were variously stained with haematoxylin and eosin (H & E), for mast cell tryptase and with the lectins lPHA and PTL-11 (10,11).…”
Section: Methodsmentioning
confidence: 99%